Mujawwad Extracurricular Activities Management in Improving Student's Interest and Talent - Rudi Hasibuan; Fachruddin Azmi; Yahfizham Yahfizham (Tarbawi, 2021)
This study aims to determine the management of Mujawwad extracurricular activities in increasing the interests and talents of students at the Integrated Islamic Private Junior High School Nurul 'Azizi Medan. This research is a qualitative research. The data collection technique is done by interview, observation, documentation study and triangulation. The sources of data in this study are the Principal, Teachers and Students. The results showed that the Integrated Islamic Private Junior High School Nurul 'Azizi Medan had implemented management in Mujawwad extracurricular activities in increasing students' interests and talents, this can be seen from the management functions that apply these functions including planning, implementation and evaluation. The planning of the first phase of the Mujawwad extracurricular program was carried out through formal meetings involving school officials, principals, school principals for student affairs and the Qur’an Coordinator who were presented in the preparation of Mujawwad extracurricular program planning. At the meeting, the first thing that was determined was the implementation schedule, implementation achievements and methods used in Mujawwad extracurricular activities. The implementation of Mujawwad extracurricular management activities at the Nurul 'Azizi Integrated Islamic Private Junior High School Medan was first carried out at the beginning of the new academic year. This activity was carried out to socialize the Mujawwad extracurricular activity program with new students.